O objeto direto anafórico na fala matagrandense e paulistana: um estudo comparativo - Mendonça, Valdenice de Anucena (2004)
This study aims to analyze the strategies of performance of the anaphoric direct object in its substitution to the third person accusative clitic in the speech of the town of Mata Grande, State of Alagoas, Brazil. That was made comparing the quantitative results of two social factors of our searching, age and schooling level, with the results from speech data in the city of São Paulo, brought up by the corpus collected by Duarte (1986). Thus we were based on the methodology and theory of variationist sociolinguistics and the principles and parameters theory. The first one aims to search, describe and explain the speech variation grades, making up the relation between the social context and the linguistic context of the speaker; the second one has given theoretical support to studies in comparative syntax. On the way to elaborating our corpus, we collected data of both male and female 12 speakers of Mata Grande, divided into three age ranges and with different schooling levels. The results were very meaningful once we established that the language spoken in Mata Grande suffers a process of change and confirmed that the studied phenomenon is simultaneously occurring at the two regions, owning similar linguistic features.